Cyberbullying trends in education: Analyzing patterns and shaping future solutions - Nur Shamsiah, Abdul Rahman; Mohd Faizal, Ab Razak; Noor Azida, Sahabudin; Rabatul Aduni, Sulaiman (Politeknik Negeri Padang, 2025)
Cyberbullying has received a lot of attention in the educational community because of how quickly digital technology is evolving. This study aims to investigate the development trends and focal points of research on cyberbullying, particularly in science education, using data from the Scopus database from 2022 to 2024. The study evaluates database records using bibliometric analysis, qualitative, and quantitative methodology. Scopus was used as the primary source in querying the Dimensions and Publish or Perish (PoP) databases. The output was visualized using VOSviewer. The query was done for article titles, abstracts, and keywords using the terms "student" and "cyberbullying". The outcome of the bibliometric analysis was a substantial development of studies on cyberbullying in schools, concentrating on issues like strategies to design safer online learning platforms, the psychological consequences of cyberbullying, and mitigating online harassment. Studies clusters that investigate to what extent cyberbullying influences the motivation level and performance of students, to what extent digital literacy plays a downregulating role for mitigating ongoing online harassment, and how science education curricula can integrate anti-cyberbullying. cultures were searched with VOS viewer’s visual analysis. These findings suggest that cyberbullying in science education is a research field that is expanding rapidly and has significant implications for pedagogic practice. The current study provides a comprehensive account of recent advances in research into cyberbullying in education and useful information for future research.